Rural Post-Earthquake Resettlement Mode Choices: Empirical Case Studies of Sichuan, China - Zhao, Lei; Zhou, Sifan; Zhong, Jinglin; Ao, Yibin; Wang, Yan; Wang, Tong; Chen, Yunfeng (Frontiers in Public Health, 2022)
Earthquakes occur frequently in rural areas of Sichuan, China, which cause huge damages and high mortality. The built environment plays a significant role in providing residents with safe and resilient settlements in such areas. There is yet little research on how rural families in developing countries cope with geological disasters like earthquakes and how built environment factors would influence their resettlement choices which directly affect their quality of life afterwards. Urban planning activities should be accompanied by these insights to design and create human-centric resettlements accordingly. In this study, the resettlement choices after three major earthquakes in Sichuan were studied for this reason. Random sampling and face-to-face questionnaire surveys were combined with factor analysis and binary logistic regression to understand the resettlement modes desired by the residents and the influencing factors. The results show that residents who have lived in their current places long and whose houses were not built recently are more likely to choose the in-situ resettlement. Accessibility to employment and public services has a significant impact on residents' choice of in-situ resettlement or reallocated resettlement, so does the previous resettlement experience. The research results can provide useful suggestions for Chinese rural area post-earthquake resettlement planning following a human-centric approach with empirical data.